Liver cell transplantation in severe infantile oxalosis: a potential bridging procedure to orthotopic liver transplantation? - Beck, Bodo Bernhard; Meyburg, Jochen (Nephrology, dialysis, transplantation, 2012)
Abstract: Background: The infantile form of primary hyperoxaluria type I (PHI) is the most devastating PH subtype leading to early end-stage renal failure and severe systemic oxalosis. Combined or sequential liver–kidney transplantation (LKTx) is the only curative option but it involves substantial risks, especially in critically ill infants. The procedure also requires resources that are simply not available to many children suffering from PHI worldwide. Less invasive and less complex therapeutic interventions allowing a better timing are clearly needed. Liver cell transplantation (LCT) may expand the narrow spectrum of auxiliary measures to buy time until LKTx for infants can be performed more safely. Methods: We performed LCT (male neonate donor) in a 15-month-old female in reduced general condition suffering from systemic oxalosis. Renal replacement therapy, initiated at the age of 3 months, was complicated by continuous haemodialysis access problems. Living donor liver transplantation was not available for this patient. Plasma oxalate (Pox) was used as the primary outcome measure. Results: Pox decreased from 104.3 ± 8.4 prior to 70.0 ± 15.0 μmol/L from Day 14 to Day 56 after LCT. A significant persistent Pox reduction (P < 0.001) comparing mean levels prior to (103.8 μmol/L) and after Day 14 of LCT until LKTx (77.3 μmol/L) was seen, although a secondary increase and wider range of Pox was also observed. In parallel, the patient’s clinical situation markedly improved and the girl received a cadaveric LKTx 12 months after LCT. However, biopsy specimens taken from the explanted liver did not show male donor cells by amelogenin polymerase chain reaction. Conclusions: With due caution, our pilot data indicate that LCT in infantile oxalosis warrants further investigation. Improvement of protocol and methodology is clearly needed in order to develop a procedure that could assist in the cure of PHI.
Published: 28 January 2012
Gesehen am 07.11.2018